Analysis And Design Of Enterprise Architecture Using Togaf Adm In Product Development Division And Production And Operation Division Of Pt. Inti (persero) - Inas Nisrina; Yuli Adam Prasetyo; Rahmat Mulyana (eProceedings of Engineering, 2016)
PT. Industri Telekomunikasi Indonesia (Persero) or PT. INTI (Persero) is a state-owned enterprise in telecommunication industry as a case study of this research, has already a manufacturing business But PT. INTI wants to make the business is bigger for the long-term target plan. Thus, to make it happen, EA can help the enterprise to align the business and IT, and also to see the gap between the baseline and target architectures, in order to make the business improvement. These architectures include the business, data, information, and technology architecture. In this research, The Open Group Architecture Framework’s Architecture Development Method (TOGAF ADM) is used. This framework includes the guidance of the overall process in designing architectures, with a cycle-based method and some phases. This research consists of 6 phases of TOGAF ADM (from Preliminary Phase until the Opportunities & Solutions Phase), and the study is about the Product Development and Production & Operation Division in PT. INTI. Manufacturing Execution System can help to improve the manufacturing execution process operations, to improve the manufacturing business of the enterprise. Keywords: Enterprise Architecture, PT. INTI, TOGAF ADM, Product Development Division, Production & Operation Division